2023
DOI: 10.1039/d2bm01199a
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive nanofiber buttresses as local drug delivery devices

Abstract: Electrospun nanofibers are a 3D scaffold of choice for many drug delivery devices due to their high surface area, significant capacity for drug payload, ease of in situ placement, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…Variations in pH across different parts of the human body inspire the use of pH-sensitive materials, like the Eudragit polymer family, for targeted drug delivery [ 96 , 97 ]. For instance, the gastric juice pH ranges from 0.9 to 1.8, contrasting with the intestinal tract’s pH of around 7.…”
Section: Drug Release Modes Of Drug-loaded Nanofibersmentioning
confidence: 99%
“…Variations in pH across different parts of the human body inspire the use of pH-sensitive materials, like the Eudragit polymer family, for targeted drug delivery [ 96 , 97 ]. For instance, the gastric juice pH ranges from 0.9 to 1.8, contrasting with the intestinal tract’s pH of around 7.…”
Section: Drug Release Modes Of Drug-loaded Nanofibersmentioning
confidence: 99%
“…In today's technological milieu, it is commonly acknowledged that stimuli‐sensitive systems with controlled drug release are feasible. Both exogenous and endogenous stimuli are used for the sake of this objective, however, the most frequent trigger is endogenous pH 184 . Functionalizing the fundamental pH‐responsive polymers with chemical moieties that render these polymers dually responsive to a variety of stimuli makes the targeting efficiency more precise.…”
Section: Applications Of Polyelectrolytes In Drug Deliverymentioning
confidence: 99%
“…Both exogenous and endogenous stimuli are used for the sake of this objective, however, the most frequent trigger is endogenous pH. 184 Functionalizing the fundamental pH-responsive polymers with chemical moieties that render these polymers dually responsive to a variety of stimuli makes the targeting efficiency more precise. This phenomenon has been investigated by Xu et al A pH and glutathione-triggered drug delivery system against breast cancer was developed by conjugating doxorubicin with polyethylene glycol linked through disulfide bonds and cis-aconitic anhydride.…”
Section: Drug Delivery To the Malignant Tissuesmentioning
confidence: 99%
“…Ismail Altinbasak et al reported a pH-responsive nanofiber scaffold synthesized by electrospinning using a polymer composed of a hydrolysable, acid-sensitive, and side-chain trimethoxybenzaldehyde-protected acrylate main chain. At physiologically relevant pH = 6.5 in the extracellular tumor environment, the scaffold transitions from a hydrophobic state to a hydrophilic state, leading to hydrolysis of the side chains and an approximately three-fold increase in fiber diameter, thereby releasing the drug encapsulated within the nanofiber scaffold [ 254 ].…”
Section: Multiresponse Intelligent Drug Delivery Systems Based On Nan...mentioning
confidence: 99%